Electrospun Nanofiber and Cryogel of Polyvinyl Alcohol Transdermal Patch Containing Diclofenac Sodium: Preparation, Characterization and In Vitro Release Studies - Shafizah Sa'adon; Mohamed Nainar Mohamed Ansari; Saiful Izwan Abd Razak; Abdul Halim Mohd Yusof; Ahmad Athif Mohd Faudzi; Suresh Sagadevan; Nadirul Hasraf Mat Nayan; Joseph Sahaya Anand; Khairul Anuar Mat Amin (MDPI AG, 2021)
Transdermal drug delivery systems (TDDS) have drawn more interest from pharmaceutical scientists because they could provide steady blood levels and prevent the first-pass metabolism over a longer period. Polyvinyl alcohol (PVA) has been widely used in this application due to its biocompatibility, non-toxicity, nanofiber and hydrogel-forming ability. Despite those benefits, their morphology would easily be destroyed by continuous water absorption and contribute to burst drug release due to its hydrophilicity. The aim of this study was to prepare the diclofenac sodium (DS)-medicated dual layer PVA patch using a combination of electrospinning and cryogelation (freeze-thaw) methods to improve the physicochemical properties and drug compatibility and investigate the release of the DS-medicated dual layer PVA patch. Morphological observations using scanning electron microscopy (SEM) verified the polymer−polymer interaction between both layers, whereas Fourier transform infrared (FTIR) spectroscopy has demonstrated the compatibility of DS in PVA matrix up to 2% w/v of PVA volume. The DS loads were found amorphously distributed efficaciously in PVA matrix as no visible spectra of DS-PVA interaction were detected. The DS-medicated dual layer PVA patch with a thicker nanofiber layer (3-milliliter running volume), three freeze-thaw cycles and 2% DS loading labeled as 2%DLB3C show the lowest swelling capacity (18.47%). The in vitro assessment using Franz diffusion cells showed that the 2%DLB3C indicates a better sustained release of DS, with 53.26% of the DS being released after 12 h. The 2%DLB3C owned a flux (Jss) of 0.256 mg/cm2/h and a permeability coefficient (Kp) value of 0.020 cm/h. Thus, the results demonstrate that DS-medicated dual layer PVA patches prepared via a combination of electrospinning and cryogelation are capable of releasing drugs for up to 24 h and can serve as a drug reservoir in the skin, thereby extending the pharmacologic effects of DS.